2019
DOI: 10.1364/prj.7.000828
|View full text |Cite
|
Sign up to set email alerts
|

Ge-on-Si modulators operating at mid-infrared wavelengths up to 8  μm

Abstract: We report mid-infrared Ge-on-Si waveguide based PIN diode modulators operating at wavelengths of 3.8 μm and 8 μm. Fabricated 1 mm-long electro-absorption devices exhibit a modulation depth of >35 dB with a 7 V forward bias at 3.8 μm, and a similar 1 mm-long Mach-Zehnder modulator has a V π •L of 0.47 V•cm. Driven by a 2.5 V pp RF signal, 60 MHz On-Off Keying modulation was demonstrated. Electro-absorption modulation at 8 μm was demonstrated preliminarily, with the device performance limited by large contact se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…When driven by a RF signal, 60 MHz OOK modulation was demonstrated in both the EAM and MZM devices. An EAM device has also been demonstrated at a wavelength of 8 μm, with a 2.5 dB modulation depth for a 7 V DC forward bias in a 2-mm-long PIN diode [24]. The measurements indicated that the injected free carrier absorption was more than 4.9 times greater at 8 μm than at 3.8 μm for the same carrier concentration, which was consistent with the theoretical predictions of [21].…”
Section: E Ge Injection Modulatorssupporting
confidence: 77%
“…When driven by a RF signal, 60 MHz OOK modulation was demonstrated in both the EAM and MZM devices. An EAM device has also been demonstrated at a wavelength of 8 μm, with a 2.5 dB modulation depth for a 7 V DC forward bias in a 2-mm-long PIN diode [24]. The measurements indicated that the injected free carrier absorption was more than 4.9 times greater at 8 μm than at 3.8 μm for the same carrier concentration, which was consistent with the theoretical predictions of [21].…”
Section: E Ge Injection Modulatorssupporting
confidence: 77%
“…Below 9 Gbit s −1 the signal is error-free. Given that a BER ≤ 4 × 10 −3 can be corrected using error correction codes without excessive overhead, [3,27] we achieved an error-free transmission up to 10 Gbit s −1 which is far beyond the state-of-theart at this wavelength in free-space using either external [28] or direct [3] modulation, without any postprocessing nor equalization.…”
Section: Data Transmissionmentioning
confidence: 99%
“…It is relevant to note that FEC has a step-like efficiency, so BER below the critical value will be greatly enhanced while BER above the critical value will remain mostly unchanged 50 and consequently, the privacy of the transmission is not threatened by this technique. Even though CMo gave better results in terms of BER with other semiconductor lasers 54 , it would be interesting to compare this method with chaos masking, for instance using mid-infrared external modulators that already achieve dozens of Mbits/s 55 . Meanwhile, several opportunities can be envisioned in order to enhance the real-field performances of this experimental proof-of-concept.…”
Section: Discussionmentioning
confidence: 99%